Strengthening Rural Local Institutional Capacities for Sustainable Livelihoods and Equitable Development - Uphoff, Norman; Buck, Louise (Washington, DC, 2012)
In considering the contribution that Rural Local Institutions (RLIs) can make to Sustainable Livelihoods (SLs), authors bring together two important concerns that emerged among development practitioners in the 1980s and 1990s, respectively. RLIs are important for addressing and mitigating factors of insecurity and instability, dealing in particular with various aspects of vulnerability. RLIs can also support participation (voice), conflict mitigation (peace), and external linkage (market expansion). Generally they produce a variety of public goods at local levels even if focused on narrower objectives. Households and communities are multiply linked, or potentially linked, having many economic, social, information and other connections with distant kin, enterprises and diverse institutions within the country and often internationally. This paper focused on institutions that in fact have some organizational structure, seeking to make them more amenable to introduction and improvement. These are institutions that can have leadership and purposeful direction. Those of which this cannot be said are certainly of similar importance; however, they function very differently.